Rhetorical move structures and politeness strategies employed in request and refusal emails by international students in a Thai ELF context - Ying Liu; Ngo Dai De Nguyen; Huu Chanh Nguyen; Anchalee Wannaruk (Cogent Education)
Thailand is becoming a popular destination for international students, where English is used as a Lingua Franca (ELF) in academics and daily life. Email writing is a critical skill for their studies and future careers, requiring appropriate rhetorical move structures and politeness strategies. Requests and refusals, as face-threatening acts (FTAs), pose challenges for second language (L2) learners, particularly when addressing higher-status individuals via email. This study examined the rhetorical move structures and politeness strategies in request and refusal emails written by international students in a Thai ELF context, along with underlying factors. Data from the writing task and interviews revealed a new move, and some previously conventional or obligatory moves became optional compared to existing frameworks. Positive strategies were more common in request emails, while negative strategies were prevalent in refusals. As for factors in the choice of politeness strategies, the recipient’s social distance, pragmatic transfer, and language input were found to coincide with the previous studies, yet the addressee’s background was found to be a new factor. The findings may contribute to the existing literature in the field of social linguistics and pragmatics. Pedagogical implications regarding emails’ rhetorical move structures, politeness strategies, and cross-cultural pragmatic awareness are suggested.